PENGARUH PEMBERIAN EKSTRAK BLACK GARLIC (Allium sativum) SEBAGAI PENGHAMBAT ATEROSKLEROSIS YANG DIINDUKSI MINYAK JELANTAH - Inna Rahmayanti Perwisa (Yayasan Pendidikan Medika Indonesia, 2020)
The need for cooking oil is not supported by an affordable price. People choose to use waste cooking oil repeatedly to save costs. Repeated heating will cause the formation of free radicals which can facilitate the formation of atheroclerotic lesions. Black Garlic as a high antioxidant substance can inhibit and prevent oxidative reactions. Allicin or (+) S-(2-propenyl)-L-cysteine sulfoxide is a precursor to the substance allicin (alil 2-propenethiosulphinate atau dialil thiosulfinate). These compounds can be used in neutraceutical as well as medical applications such as antioxidant, antimicrobial and hypolipidemic activity. Black garlic which contains several bioactive compounds such as S-allyciysteine, vitamins, phenolic acids, and favonoid compounds as used cooking oilantioxidants can be an excellent natural candidate in preventing and repairing atherosclerotic lesions and also has the benefit of lowering triglyceride levels, total cholesterol, and LDL-cholesterol and increase HDL-cholesterol levels.